Social relations and contact with general practitioner in a middle-aged Danish population: a prospective register- and survey-based cohort study - Anne Sophie Bech Mikkelsen; Rikke Lund; Volkert Siersma; Terese Sara Høj Jørgensen; Ulla Christensen; Maria Kristiansen (BMC, 2022)
Abstract Background Findings about the relationship between individuals' social relations and general practitioner (GP) contact are ambiguous as to whether weak social relations are associated with an increased or decreased consultation pattern. Furthermore, social relations may affect GP contact differently for men compared to women, between socioeconomic groups and according to perceived need. The overall aim of the study is to examine the association between functional aspects of social relations, perceived emotional and instrumental social support, the tendency to consult a GP and the frequency of GP contact. Methods The study comprised 6911 individuals aged 49-61 at baseline from the Copenhagen Aging and Midlife Biobank (CAMB). We conducted a two-part regression to explore the association between perceived emotional and instrumental social support and GP contact (tendency and frequency), controlling for age, sex, occupational social class, cohabitation status and number of morbidities. Results Results show no overall effect of the perceived social support aspects of social relations on GP contact independent of health-related needs. Conclusions Our results do not support that perceived social support, reflecting functional aspects of social relations, are associated with general practitioner contact among middle-aged people. Trial registration The study has been registered and approved by the Danish Data Protection Agency and the local ethical committee (approval No.H-A-2008-126 and No. 2013-41-1814).Keywords: social relations, perceived social support, healthcare utilisation, general practitioner, middle-aged